Short-term outcomes of COVID-19 in pregnant women unvaccinated for SARS-CoV-2 in the first, second, and third trimesters: a retrospective study - Guleroglu, Filiz Yarsilikal; Atalmis, Hatice Argun; Bafali, Icten Olgu; Dikdere, Gulser Bingol; Dikdere, Irfan; Ekmez, Murat; Kaban, Alpaslan; Karasabanoglu, Fatma; Atas, Busra Seker; Selvi, Esra; Sumnu, Gulay; Topaktas, Merve; et al. (São Paulo Medical Journal, 2023)
BACKGROUND: Coronavirus disease 2019 (COVID-19) may be asymptomatic or symptomatic in pregnant women. Compared to non-pregnant reproductive-aged women, symptomatic individuals appear to have a higher risk of acquiring severe illness sequelae. OBJECTIVES: We assessed the clinical and laboratory characteristics and outcomes of pregnant COVID-19 patients unvaccinated for severe acute respiratory syndrome coronavirus 2 according to the trimester of pregnancy. DESIGN AND SETTING: This was a retrospective observational study conducted in a tertiary-level hospital in Turkey. METHODS: This retrospective study reviewed the clinical and laboratory characteristics and outcomes of 445 pregnant COVID-19 patients hospitalized during the first, second, and third trimesters of pregnancy and 149 other pregnant women as controls in a tertiary center from April 2020 to December 2021. All participants were unvaccinated. RESULTS: Overall, the study groups were comparable in terms of baseline clinical pregnancy characteristics. There was no clear difference among the study participants with COVID-19 in the first, second, and third trimesters of pregnancy. However, a considerably high number of clinical and laboratory findings revealed differences that were consistent with the inflammatory nature of the disease. CONCLUSIONS: The study results reveal the importance of careful follow-up of hospitalized cases as a necessary step by means of regular clinical and laboratory examinations in pregnant COVID-19 patients. With further studies, after implementing vaccination programs for COVID-19 in pregnant women, these data may help determine the impact of vaccination on the outcomes of pregnant COVID-19 patients.